2003
DOI: 10.1034/j.1398-9995.2003.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of ketotifen on eotaxin‐dependent activation of eosinophils: consequences for allergic eye diseases

Abstract: Through inhibition of chemotaxis, ketotifen might limit the number of eosinophils at the inflammation site during allergic reaction. Furthermore, inhibition by ketotifen of main inflammatory mediators release suggests a potential role of the drug in limiting the pathological potential of eosinophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Many studies have shown an increased production of ROS in asthma, allergic rhinitis, and atopy dermatitis, which contributes, in part, to tissue injury at sites of inflammation (Bowler and Crapo, 2002). A respiratory burst of eosinophils activated by eotaxin has been demonstrated, leading to production of ROS (Woerly et al, 2003;Elsner et al, 1998). We examined the effect of CAPE on generation of ROS, as described in Fig.…”
Section: Cape Diminishes the Ros Generation In Bal Fluidmentioning
confidence: 99%
“…Many studies have shown an increased production of ROS in asthma, allergic rhinitis, and atopy dermatitis, which contributes, in part, to tissue injury at sites of inflammation (Bowler and Crapo, 2002). A respiratory burst of eosinophils activated by eotaxin has been demonstrated, leading to production of ROS (Woerly et al, 2003;Elsner et al, 1998). We examined the effect of CAPE on generation of ROS, as described in Fig.…”
Section: Cape Diminishes the Ros Generation In Bal Fluidmentioning
confidence: 99%
“…Ketotifen, indeed, prevents late-phase anaphylactic events such as platelet-activating factor (PAF)-mediated reactions 11 as well as eosinophil chemotaxis and activation. 12 This paper reports the effects of ketotifen fumarate (Zaditen Ophtha R , 0.025% ophthalmic solution), olopatadine (Patanol R , 0.1% ophthalmic solution), and levocabastine (Levophta R , 0.05% ophthalmic suspension) in two different animal models. Ocular active anaphylaxis was studied in guinea pigs and ocular immediate hypersensitivity in albino rats.…”
Section: Introductionmentioning
confidence: 99%
“…The production of reactive oxygen species (ROS) from eosinophils was analyzed as previously described by a luminol-dependent chemiluminescence assay (29). Purified eosinophils (3 ϫ 10 5 cells) were incubated in 25 l of RPMI 1640 without phenol red in white 96-well plates for 30 min at 37°C in 5% CO 2 .…”
Section: Eosinophil Degranulation Assaymentioning
confidence: 99%